The white-chinned petrel procellaria aequinoctialis population of the Falkland Islands - Reid, Tim A. (2012)
A survey of all known colonies of the White-chinned Petrel Procellaria aequinoctialis within the Falkland Islands was conducted during the austral summers of 2004/05 and 2005/06. From these surveys, a minimum population of 55 pairs was observed. Most of these were on Kidney and New islands, with a very small colony on Bottom Island in Port William. Although evidence of a decrease in the size of the population on Kidney Island is limited, the population in the Falklands is likely historically to have been small.